Health insurance in sub-Saharan Africa: a scoping review of the methods used to evaluate its impact - Degroote, Stéphanie; Ridde, Valéry; De Allegri, Manuela (Applied health economics and health policy, 2019)
We conducted a scoping review with the objective of synthesizing available literature and mapping what designs and methods have been used to evaluate health insurance reforms in sub-Saharan Africa. We systematically searched for scientific and grey literature in English and French published between 1980 and 2017 using a combination of three key concepts: “Insurance” and “Impact evaluation” and “sub-Saharan Africa”. The search led to the inclusion of 66 articles with half of the studies pertaining to the evaluation of National Health Insurance schemes, especially the Ghanaian one, and one quarter pertaining to Community-Based Health Insurance and Mutual Health Organization schemes. Sixty-one out of the 66 studies (92%) included were quantitative studies, while only five (8%) were defined as mixed methods. Most studies included applied an observational design (n = 37; 56%), followed by a quasi-experimental (n = 27; 41%) design; only two studies (3%) applied an experimental design. The findings of our scoping review are in line with the observation emerging from prior reviews focused on content in pointing at the fact that evidence on the impact of health insurance is still relatively weak as it is derived primarily from studies relying on observational designs. Our review did identify an increase in the use of quasi-experimental designs in more recent studies, suggesting that we could observe a broadening and deepening of the evidence base on health insurance in Africa over the next few years.